Sonographic Evaluation of Pelvic Pain in Gravid and Non-Gravid Uterus - Hira Rashad, Syeda Khadija, Muhammad Yousaf Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate sonographically pelvic pain and contribution of pelvic ultrasound in diagnosing pelvic pathologies in females with gravid and non-gravid uterus. Study Design: Cross-sectional analytical study Place and Duration: Sami Diagnostic and Waraich Ultrasound center Jauharabad (Khushab). Duration of study was 9 months. Methodology: Convenient sampling technique was used and 100 patients were enrolled. Toshiba Xario and Hitachi Aloka ultrasound machines were used. Study included females with gravid uterus, nongravid uterus, and those with pelvic pain present and also with absent pain. It excluded females with non-gynecological complaints. Both transabdominal and transvaginal ultrasound modalities were used. Longitudinal, transverse and oblique views were taken. Based on sonographic findings, diagnosis was made and image recorded. SPSS version 22.0 was used for data analysis. Results: In patients with gravid uterus pelvic pain was present in 23 (67.6%) and absent in 11 patients (32.4%). In non-gravid uterus pelvic pain was present in 64 (97.0%) and absent in 2 (3.0%). Most common finding was Intramural uterine fibroid (12%) with pain present in 8 and absent in 4 patients followed by hemorrhagic ovarian cyst HOC (10%) with pelvic pain present in 9 and absent in 1, simple ovarian cysts (7%) caused pelvic pain in 7 patients and in subserosal fibroid (6%) pelvic pain was present in 4 patients and absent in 2 patients. 10% females were presented with pelvic pain but showed normal ultrasound findings. Conclusion: Ultrasound is modality of choice to determine the pelvic pathologies in females. Pelvic pain was present more in non-gravid females. Most incident etiology causing pelvic pain was intramural fibroids. Age factor is one of the most effecting factors for the pelvic pain in gravid uterus. Keywords: Ultrasound, Pelvic pain, Fibroids, Hemorrhagic ovarian cyst, Ovarian cyst